Long-term outcomes of arthroscopic management of femoroacetabular impingement syndrome: a systematic review - Migliorini, Filippo; Vaishya, Raju; Simeone, Francesco; Memminger, Michael Kurt; Betsch, Marcel; Pasurka, Mario (Archives of Orthopaedic and Trauma Surgery, 2025)
Introduction: Femoroacetabular impingement (FAI) syndrome is a condition characterised by irregularities in the femur or acetabular rim, leading to hip pain, increased risk of osteoarthritis (OA), and potential need for total hip arthroplasty (THA). Non-surgical treatments are the first-line approach. However, arthroscopic surgery has become more prevalent due to its promising short- and medium-term outcomes. Recent meta-analyses suggest that hip arthroscopy may offer superior results compared to non-operative treatments, though follow-up periods in these studies have been limited to 12 months. This systematic review aims to evaluate the long-term effectiveness of arthroscopic management for FAI syndrome, hypothesising that it will significantly improve patient-reported outcomes (PROMs) over a follow-up period exceeding ten years. Methods: The review focused on studies published in peer-reviewed journals with a minimum follow-up of 120 months and assessed outcomes such as PROMs and complication rates. It adhered to PRISMA guidelines and used the PICOT algorithm to evaluate the literature. Data extraction covered study characteristics, PROMs, and complications. Statistical analyses were conducted using IBM SPSS software to summarise continuous and dichotomous data. Results: Of 1,245 identified articles, 7 were included after rigorous screening. Risk of bias assessment with the ROBINS-I tool revealed a serious or moderate risk of bias due to confounding, although overall methodological quality was acceptable. Data from 478 patients showed significant improvements in PROMs from baseline to follow-up. Conclusion: This systematic review indicates that arthroscopic management for FAI syndrome significantly improves PROMs with a mean follow-up of approximately 130 months. Nevertheless, 32% of patients required THA within ten years, underscoring the importance of careful patient selection and consideration of factors like OA and age. While conservative treatments such as physical therapy may yield comparable short-term outcomes, recent evidence suggests that arthroscopy provides superior results, particularly for younger patients and those without preoperative OA. Level of evidence: Level II, systematic review and meta-analysis.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Arthroplasty; Arthroscopy; FAI syndrome; Femoroacetabular impingement; Hip